PENGARUH MOTIVASI, KOMPENSASI, KOMUNIKASI DAN PRODUKTIVITAS KERJA TERHADAP KINERJA KARYAWAN PT PRATITHA TITIANNUSANTARA (PT PTN) KOTA PANGKALPINANG - Akbar, Khalif; Zamhari; Astuti, Nelly (Jurnal Progresif Manajemen Bisnis, 2021)
The title of this thesis in Indonesian: "Pengaruh Motivasi, Kompensasi, Komunikasi dan Produktivitas Kerja Terhadap Kinerja Karyawan PT Pratitha Titiannusantara (PT PTN) Kota Pangkalpinang”. This research was conducted from November 2020 to February 2021 in the city of Pangkalpinang. This thesis consists of 92 pages without attachments. The purpose of this study was to determine how much influence motivation, compensation, communication and work productivity on employee performance either partially or simultaneously at PT. Pratitha Titiannusantara. This study uses a saturated sampling technique because the sample used is less than 30 people representing the population of PT Pratitha Titiannusantara. The variables used are motivation, compensation, communication and work productivity as the independent variable and employee performance as the dependent variable which is then developed independently according to the indicators. The data analysis method used is multiple linear regression analysis and as a tool in statistical data processing the SPSS version program is used. 22. The results of the research conducted show that: (1) Partial t test conducted on motivation shows that motivation has a positive influence on employee performance; (2) Partial t test conducted on compensation shows that compensation does not have a positive effect on employee performance; (3) partial t test conducted on communication shows that communication does not have a positive influence on employee performance; (4) partial t test conducted on work productivity shows that work productivity does not have a positive effect on employee performance; (5) simultaneous F test conducted on the four independent variables states that motivation, compensation, communication and work productivity together have a positive influence on employee performance. The result of the coefficient of determination (adjust R-square) shows a value of 0.834. This value defines that 97,2% of employee performance at PT. Pratitha Titiannusantara is influenced by the variables of Motivation, Compensation, Communication and Work Productivity together, while the remaining 2,8% is influenced by external variables which are not included in this study.